In anti-CCP+ at-risk individuals, radiographic bone erosions are uncommon and are not associated with the development of clinical arthritis. (13th December 2020) - Di Matteo, Andrea; Mankia, Kulveer; Nam, Jacqueline L; Cipolletta, Edoardo; Garcia-Montoya, Leticia; Duquenne, Laurence; Rowbotham, Emma; Emery, Paul
Abstract: Objectives: To investigate the prevalence, distribution and predictive value for the development of inflammatory arthritis (IA) of conventional radiography (CR) bone erosions (BE) in anti-CCP positive (CCP+) at-risk individuals with musculoskeletal (MSK) symptoms but without clinical synovitis. Methods: Baseline CR of the hands and feet of 418 CCP+ at-risk individuals were analysed. The presence of US-BE was explored in the anatomical areas in which CR-BE were reported. Hands and feet CR at the time of progression were analysed in a subset of individuals who developed IA (73/123, 59.3%). Logistic regression analyses were performed to calculate the predictive value of baseline CR-BE for the development of IA in 394 CCP+ individuals with ≥1 follow-up visit. Results: BE were detected in 17/418 (4.1%) CCP+ at-risk individuals (median Simple Erosions Narrowing Score-BE = 2.0, IQR: 1.0–2.0; median Sharp van der Heijde score-BE = 4.0, IQR: 3.0–8.5), most frequently in the foot joints (11/17, 64.7% individuals). A total of 123/394 (31.2%) CCP+ at-risk individuals developed IA; 7/17 (41.2%) with, and 116/377 (30.8%) without BE on CR ( P  = 0.37). US-BE were found in 4/7 (57.1%) individuals with CR-BE who developed IA, but only in 1/10 (10.0%) who did not. At the time of progression, new BE were detected in 4/73 (5.5%) CCP+ individuals on repeated CR. In the regression analyses, baseline CR-BE were not predictive for the development of IA. Conclusions: In CCP+ at-risk individuals with MSK symptoms, CR-detected BE are uncommon and do not predict the development of IA.